Pengaruh Model Pembelajaran Think Talk Write Terhadap Kemampuan Kognitif Peserta Didik Kelas VIII Dalam Pembelajaran IPS - Nur, Muhammad Saifuddin (Jurnal Dialektika Pendidikan IPS, 2023)
In the world of education, educators often do not know the extent of the knowledge of their students so that the importance of cognitive abilities of students is often ignored even though the cognitive abilities of students can be a standard for improving the quality of education. The existence of a learning model can be an alternative to create success in learning. This study aims to determine the effect of the think, talk, write learning model on the cognitive abilities of students in social studies learning. The think, talk, write learning model is a strategy which aims to encourage students to be able to think, speak, and write down the results of their ideas in the thinking stages they have passed. The research method used in this study was a quasi-experimental quantitative study with a non-equivalent control group design. Samples were taken using a purposive cluster sampling technique. In this case the researcher took a sample of 60 respondents. The population in this study were all class VIII students at SMP Negeri 44 Surabaya for the 2022/2023 academic year, namely 237 students. The data collection technique was carried out by distributing questionnaires directly. This study used descriptive statistical analysis with data processing in the form of validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis testing using the help of the SPSS version 25 assistance program. The results obtained from the paired sample t test obtained sig. 0.0000 <0.005 so that H0 is rejected and H1 is accepted which means that there is a significant influence between variables so that the result is that there is an influence of the think, talk, write learning model on the cognitive abilities of class VIII participants in social studies learning.